An investigation of some persistent organic pollutants in loggerhead sea turtles ( Caretta caretta ) - Kuzukiran, Ozgur; Simsek, Ilker; Kara, Erdem; Yurdakok-Dikmen, Begum; Boztepe, Ummu Gulsum; Toprak, Meryem; Filazi, Ayhan (Pergamon-Elsevier Science Ltd, 2024)
The study assessed persistent organic pollutants (POPs) in Caretta caretta turtles along Turkish coasts, analyzing bioaccumulation in accessible organs and discerning sex-related differences. Ten adult turtles (5 males, 5 females) from Mugla province were sampled post-mortem. Various tissues were analyzed for organochlorine pesticides (OCPs), polychlorinated biphenyls (PCBs), polybrominated diphenyl ethers (PBDEs), and polycyclic aromatic hydrocarbons (PAHs) using gas chromatography -mass spectrometry. DDT distribution showed no sexbased difference, with concentrations highest in fat tissue followed by liver, kidney, muscle, spleen, and heart. Male PCB concentrations ranked highest in fat, followed by kidney, liver, spleen, muscle, and heart, while females showed a similar trend. PAH concentrations were highest in fat for both sexes, followed by various organs. Limited PBDE concentrations hindered comprehensive evaluation. Overall, C. caretta act as effective bioindicators for monitoring environmental pollution, with certain POPs exhibiting sex and organ-based variations.
Keywords: Sea turtles; Endocrine disruptors; Sex; Organ; Pollution